1969
DOI: 10.2307/1948548
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Distribution of Pinus pungens, an Appalachian Endemic

Abstract: Pinus pungens is in Section Diploxylon, the hard or yellow pines. Its classification below section level varies considerably (Mirov, 1967). The range of Table Mountain pine is almost entirely within the ranges of two other hard pines, Pinus rigida and P. virginiana (Critchfield & Little, 1966). Throughout the common range of the three species, P. pungens is by far the rarest. There are large areas where it has not been reported, and, when it is present, it is usually in small populations restricted to the site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(29 citation statements)
references
References 25 publications
0
29
0
Order By: Relevance
“…In the context of SPB, fire may prevent SPB outbreaks by thinning the forests; fire also helps regeneration of young pines. Many past research have found that in the absence of fire, a major transformation occurred leading to the loss of pine itself as well as the numerous fire dependent ground layer species (e.g., Zobel 1969, Buckner and Turrill 1999, Xi et al 2009). Since it is impractical to allow wildfire to burn neither in public nor private forest lands, prescribed burning is a practical alternative that has been found to be effective to promote regeneration of pines (Vose et al 1993, 1995, Waldrop and Brose 1999, Waldrop et al 2000, Boyle et al 2004.…”
Section: Restoration Of Ecosystem Functions and Processesmentioning
confidence: 99%
“…In the context of SPB, fire may prevent SPB outbreaks by thinning the forests; fire also helps regeneration of young pines. Many past research have found that in the absence of fire, a major transformation occurred leading to the loss of pine itself as well as the numerous fire dependent ground layer species (e.g., Zobel 1969, Buckner and Turrill 1999, Xi et al 2009). Since it is impractical to allow wildfire to burn neither in public nor private forest lands, prescribed burning is a practical alternative that has been found to be effective to promote regeneration of pines (Vose et al 1993, 1995, Waldrop and Brose 1999, Waldrop et al 2000, Boyle et al 2004.…”
Section: Restoration Of Ecosystem Functions and Processesmentioning
confidence: 99%
“…Cone serotiny in Table Mountain pine gives it an advantage over shortleaf, pitch, and Virginia pines when subjected to crown fues.6 Pitch pine has some degree of cone serotiny (Fowells 1968), a characteristic shared, in part, by shortleaf, and is more fire resistant than Virginia or Table Mountain pine due to thicker bark and dormant buds along the bole (Zobel 1969). Pitch and shortleaf pines develop a basal crook in seedlings, which also may protect them from fire (Little and Mergen 1966).…”
Section: Appalachian Mountains: Blue Ridgementioning
confidence: 99%
“…Elsewhere in southwest Virginia, relatively undisturbed Table Mountain pine stands occupied southwest slopes at 2,500 feet (762 m) and contained scarlet and chestnut oaks, sassafras, and blackgum (Williams and Johnson 1992). Within the Valley and Ridge, Table Mountain pine typically occupies steep, lower, and middle slopes, often on shale outcroppings (Zobel 1969) or ridge-capping sandstones at higher elevations.…”
Section: Appalachian Mountains: Valley and Ridgementioning
confidence: 99%
“…Prescription burning is being utilized as site preparation because it increases natural pine regeneration and seedling growth (Vose et al, 1993), releases nutrients into the soil (Stark and Steele, 1977), alters the canopy structure and light environment (Zobel, 1969;Coleman and Rieske, 2006) and reduces vegetative competition (Vose et al, 1995;Waldrop, 1997). The number and vigor of remaining seed-producing trees and the success of naturally regenerating and planted seedlings may ultimately determine regeneration success (Cain, 1993;Shelton and Cain, 2000).…”
Section: Introductionmentioning
confidence: 99%